Pengembangan E-Modul Berbasis Ethno-STEM Pada Permainan Tradisional Mbojo Mpaa Gopa Untuk Siswa SMP - PutrI Agustina; Parhaini Andriani; Mulhamah Mulhamah (FKIP Universitas Mataram, 2026)
This study aims to develop a valid, practical, and effective e-module on geometry material based on the Ethno-STEM traditional game Mbojo Mpaa Gopa. The development of this e-module uses a 4D development model consisting of four development stages, namely (1) Define, (2) Design, (3) Develop, and (4) Disseminate. In the data collection process, observations and pre-tests and post-tests were carried out. The analysis technique for testing the effectiveness of the e-module, namely by using an independent sample t-test to see the results of students' learning outcomes in geometry mathematics. The results of this study include (1) the results of expert validation of the e-module which is suitable for use with valid results in the material and design aspects, (2) the results of practicality based on teacher and student response questionnaires that have been declared to meet practical qualifications, and (3) the level of effectiveness of the e-module obtained from the t-test process that tests learning outcomes through pre-tests and post-tests. Therefore, the main conclusion of this study is that an Ethno-STEM-based e-module based on the traditional game Mbojo Mpaa Gopa was obtained that is suitable for use, categorized as valid, practical, and effective for junior high school students in geometry.